Study of two mouse mutants to identify novel neurodegenerative pathways - Finelli, M; Mattea Finelli (2010)
Neurodegenerative disorders (NDD) are an ever-increasing burden on healthcare; consequently, elucidating the mechanisms underlying neurodegeneration (ND) is critical for the development of effective treatments for these diseases. In order to unravel the molecular pathways underlying movement disorders and identify new genes involved in ND, two ataxic mouse mutants characterised by cell death in the cerebellum were studied in detail using a combination of in vitro and in vivo techniques. The robotic mouse demonstrated the key role of a transcription factor, Af4, in Purkinje cell (PC) survival and how only small changes in the levels of a single transcriptional cofactor could deleteriously affect normal cerebellum function. Expression array studies of the robotic PCs revealed the first confirmed targets of Af4-mediated transcription, including insulin-like growth factor 1 (Igf-1). It was demonstrated that Igf-1 is critical for PC survival, highlighting the role of the IGF-1 signalling pathway as a potential therapeutic target for the treatment of cerebellar ataxia in humans. Detailed analysis of the bella mutant demonstrated that ataxia and apoptotic cerebellar degeneration is caused by loss of the oxidative resistance 1 (Oxr1) gene. In vitro modelling experiments went on to show that the levels of this previously uncharacterised gene are critical for controlling the sensitivity of neuronal cells to oxidative stress (OS). Moreover, this study showed that Oxr1 was up-regulated both in human and pre-symptomatic mouse models of amyotrophic lateral sclerosis (ALS), demonstrating that Oxr1 was an early marker of ROS defence, prior to pathology, and potentially a novel neuroprotective factor in NDD. Preliminary interaction studies show that Oxr1 is likely to be a multi-functional protein that forms complexes with proteins known to be mutated in NDD. Thus, the study of both the robotic and the bella mouse has demonstrated the value of the phenotype-driven approach to investigate novel neurodegenerative pathways.